2014
DOI: 10.1155/2014/461034
|View full text |Cite
|
Sign up to set email alerts
|

Does Long-Term Use of Silver Nanoparticles Have Persistent Inhibitory Effect onH. pyloriBased on Mongolian Gerbil’s Model?

Abstract: Background. It is urgent to find alternative agents due to increasing failure rate of Helicobacter pylori (H. pylori) eradication. The study surveyed the long-term effect of silver nanoparticles (AgNP) on H. pylori based on Mongolian gerbil's model. Materials and Methods. Fifty gerbils were randomly allocated to six groups (A–F). Group (Gr) A: the gerbils were fed with broth; Gr B and D: the gerbils were fed with AgNP/clay complex (0.1% of weight); Gr C and E: the gerbils were fed with AgNP/clay complex(1% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Besides, H. pylori infection may induce extragastric diseases, making it difficult to determine the health status of experimental gerbils [ 28 ]. Though H. pylori detection before replicating the H. pylori -infected model in gerbils is necessary, we found few studies that used H. pylori -free gerbils or detected the natural infection before challenge with H. pylori [ 10 , 11 ]. However, we cannot confirm whether the animal had been infected after modelling for a long time unless the animal was sacrificed, which affected the efficiency of modelling and did not conform to the “3R principle” (reduce, refine, and replace).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, H. pylori infection may induce extragastric diseases, making it difficult to determine the health status of experimental gerbils [ 28 ]. Though H. pylori detection before replicating the H. pylori -infected model in gerbils is necessary, we found few studies that used H. pylori -free gerbils or detected the natural infection before challenge with H. pylori [ 10 , 11 ]. However, we cannot confirm whether the animal had been infected after modelling for a long time unless the animal was sacrificed, which affected the efficiency of modelling and did not conform to the “3R principle” (reduce, refine, and replace).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in many studies, H. pylori -free gerbils were not used or gerbils were not evaluated for natural infection before infection with H. pylori . It impacts the reliability and consistency of previous studies [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 98%
“…In the vast majority of the studies, spherical silver nanoparticles were used, obtained from different extracts, having various sizes: A. priceps , 5–30 nm [ 125 ]; S. xanthocarpum , 4–18 nm [ 32 , 126 ]; T. vernicifluum , 4–20 nm [ 127 ]; C. longa [ 128 ] and A. nilotica , 22–66 nm [ 124 ]; P. putida , 6–16 nm [ 35 ]; A. calamus , 5–60 nm [ 129 ]; A. nilotica , 22–55 nm [ 130 ]. The most common effect on the bacterial colonies was inhibition of growth, which was presented in six of the papers [ 124 , 125 , 127 , 128 , 131 , 132 , 133 , 134 ], followed by activation of reactive oxygen species production [ 130 , 132 ], inactivation of H. pylori urease [ 131 , 135 ], bacterial DNA fragmentation and consecutive loss of viability [ 130 ], damage to the bacterial cellular membrane [ 132 ], and activation of antioxidant activity [ 136 ].…”
Section: The Antibacterial Mechanism Of Silver Nanoparticles: An Exte...mentioning
confidence: 99%
“…There are few in vivo studies addressing the antibacterial effect of AgNPs against H. pylori (summarized in Table 3 ). One relevant study was performed in vivo by Kuo et al [ 136 ] on a batch of 8-week-old gerbils with bodyweight between 30 and 40 g which were fed with AgNp/clay complex at 0.1% of their bodyweight and another batch that was fed with the same complex at 1% of their bodyweight. In a study in 2020, Al-Bahrani et al showed a good inhibition of growth using an extract of A. bisporus [ 138 ].…”
Section: The Antibacterial Mechanism Of Silver Nanoparticles: An Exte...mentioning
confidence: 99%
“…as well as oldness and weak-ness [7]. Therefore, the main principles for insomnia treatment in Mongolian medicine are inhibition of "Haoyi" and regulation of "Sangen" [8]. The action of warm needles on the appropriate acupoints can properly alleviate "Haoyi" and balance "Sangen" for the purpose of insomnia treatment.…”
Section: Introductionmentioning
confidence: 99%